2021
DOI: 10.3390/s21196338
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Performance of Distributed Optical Fiber Sensors Embedded in Reinforced Concrete Beams under Sustained Deflection and Cyclic Loading

Abstract: This paper explores the performance of distributed optical fiber sensors based on Rayleigh backscattering for the monitoring of strains in reinforced concrete elements subjected to different types of long-term external loading. In particular, the reliability and accuracy of robust fiber optic cables with an inner steel tube and an external protective polymeric cladding were investigated through a series of laboratory experiments involving large-scale reinforced concrete beams subjected to either sustained defl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…24 and further developed by the authors of refs. 25 and 26 is used in this section to measure crack widths from the different strain measurements. Therefore, the crack width of individual bending cracks can be calculated with an accuracy of ± 20 µm based on the strain measured by the DOFS at the tensile reinforcement according to equation (1)where ε DOFS (x) is the measured strain (at the bottom reinforcement), trueε^(x) is the strain varying linearly between cracks, ρ=As/Ac,ef and α=Es/Ec are the reinforcement ratio and the modular ratio, respectively, and lt,i and lt,i+ are the ends of transmission length along which slips occurs, assumed as the valleys in the strain profile to the left and right sides of the i-th crack, w cr,i .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 and further developed by the authors of refs. 25 and 26 is used in this section to measure crack widths from the different strain measurements. Therefore, the crack width of individual bending cracks can be calculated with an accuracy of ± 20 µm based on the strain measured by the DOFS at the tensile reinforcement according to equation (1)where ε DOFS (x) is the measured strain (at the bottom reinforcement), trueε^(x) is the strain varying linearly between cracks, ρ=As/Ac,ef and α=Es/Ec are the reinforcement ratio and the modular ratio, respectively, and lt,i and lt,i+ are the ends of transmission length along which slips occurs, assumed as the valleys in the strain profile to the left and right sides of the i-th crack, w cr,i .…”
Section: Resultsmentioning
confidence: 99%
“…Brault and Hoult 23 had previously shown that multiple cracks as well as deflections could be also accurately measured using DOFS longitudinally bonded to the surface of RC beams. Further experimental work by Berrocal and Fernandez [24][25][26] revealed that by using strain measurements from robust DOFS, a good estimation of the crack width of multiple individual bending cracks and deflections in RC beams can be achieved, without the inclusion of strain transfer models between the fibre core and the substrate element, both for short and long-term monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic loads and subsequent loading to failure did not cause an impairment in the DFOS performance [29]. Fernandez et al (2021) assessed the long-term performance of robust fibre optical cables with a steel tube embedded in concrete and subjected to different loading conditions. By comparing integrated values (i.e., deflection and crack width) to DIC measurements, they concluded that the DFOS measurement remained stable over time [30].…”
Section: Introductionmentioning
confidence: 99%
“…Fernandez et al (2021) assessed the long-term performance of robust fibre optical cables with a steel tube embedded in concrete and subjected to different loading conditions. By comparing integrated values (i.e., deflection and crack width) to DIC measurements, they concluded that the DFOS measurement remained stable over time [30]. The deterioration of bond properties with increasing load cycles was investigated in the first application of DFOS with high cyclic loading [16].…”
Section: Introductionmentioning
confidence: 99%
“…This study uses advanced measurement technologies to investigate these unknowns: distributed fibre optical sensing (DFOS) and digital image correlation (DIC) have emerged as suitable tools to investigate the local structural behaviour of RC elements. [16][17][18][19][20] Three approaches to estimate tension stiffening-related properties directly from DFOS and DIC measurements are presented and applied to a highly reinforced concrete beam tested in four-point bending. Selected models for the effective reinforcement ratio and the cracking behaviour for pure bending are validated against the experimental data.…”
Section: Overview Of the Present Studymentioning
confidence: 99%